2003
DOI: 10.1093/jn/133.6.1793
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Amount of Fat in a Conjugated Linoleic Acid–Supplemented Diet Reduces Lipodystrophy in Mice

Abstract: Conjugated linoleic acid (CLA) is a naturally occurring group of dienoic derivatives of linoleic acid found in beef and dairy products. However, when 1 g CLA/100 g diet was given to mice in a low fat diet (4 g fat/100 g diet), they showed a marked decrease in fat mass, but demonstrated symptoms of lipoatrophic diabetes, i.e., marked hepatomegaly and insulin resistance. In this study, to determine whether the decrease in adipose tissue was responsible for these adverse effects, mice were fed different doses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
53
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 31 publications
13
53
0
3
Order By: Relevance
“…Similarly, despite resulting in decreased body weight, t10,c12 supplementation in mice was associated with increased serum glucose and insulin levels, whereas the c9,t11 supplementation group showed no weight loss, but lowered triglycerides and FFA (29). This study is in line with other studies in mice showing that CLA supplementation (36% t10,c12 isomer) results in marked reductions in body fat, although this was associated with the development of insulin resistance, resulting in a metabolic state resembling lipoatrophic diabetes (30,31). Similar observations have been reported by other researchers, showing that mice fed purified t10,c12 CLA or CLA mixtures develop hyperinsulinemia and fatty liver (29,(32)(33)(34).…”
Section: Effects Of Cla On Atherosclerosis and Glucose Tolerance In Asupporting
confidence: 87%
“…Similarly, despite resulting in decreased body weight, t10,c12 supplementation in mice was associated with increased serum glucose and insulin levels, whereas the c9,t11 supplementation group showed no weight loss, but lowered triglycerides and FFA (29). This study is in line with other studies in mice showing that CLA supplementation (36% t10,c12 isomer) results in marked reductions in body fat, although this was associated with the development of insulin resistance, resulting in a metabolic state resembling lipoatrophic diabetes (30,31). Similar observations have been reported by other researchers, showing that mice fed purified t10,c12 CLA or CLA mixtures develop hyperinsulinemia and fatty liver (29,(32)(33)(34).…”
Section: Effects Of Cla On Atherosclerosis and Glucose Tolerance In Asupporting
confidence: 87%
“…The impact of dietary CLA on hepatic steatosis and insulin sensitivity is controversial because of differences in species, isomer responses and degree and sensitivity to changes in adiposity (Tsuboyama-Kasaoka et al, 2003;Nagao et al, 2005;Wang et al, 2006). In this study, we investigated the effects of dietary CLA and betaine in a highly adipogenic pig model.…”
Section: Discussionmentioning
confidence: 99%
“…A toxicological study of dietary CLA in rats showed no histomorphological or hematological changes [21][22][23] . In contrast, dietary CLA leads to lipid accumulation and enlargement of the liver in mice, as a result of increased fatty acid mobilization from the adipose tissue [24][25][26] . This has not been confirmed in other animal species 5,27) .…”
Section: Discussionmentioning
confidence: 99%